2019
DOI: 10.4049/jimmunol.1801101
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Gated P2X7 Receptors Require Chloride Channels To Promote Inflammation in Human Macrophages

Abstract: Immune cells of myeloid origin show robust expression of ATP-gated P2X7 receptors, two-transmembrane ion channels permeable to Na + , K + , and Ca 2+. Receptor activation promotes inflammasome activation and release of the proinflammatory cytokines IL-1b and IL-18. In this study, we show that ATP generates facilitating cationic currents in monocyte-derived human macrophages and permeabilizes the plasma membrane to polyatomic cationic dyes. We find that antagonists of PLA 2 and Cl 2 channels abolish P2X7 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 108 publications
(130 reference statements)
0
48
0
Order By: Relevance
“…Based on findings in osteoblasts, it was proposed that P2X7 activation leads via PLD and PLA2 activation to LPA, and LPA, by activation of the LPA receptor (a GPCR), activates Rho (Panupinthu et al, 2007). Involvement of PLA2 activation in addition to an undefined Cl – channel in blebbing is supported by a recent study on macrophages (Janks et al, 2019).…”
Section: P2x7 Mediated Signaling Pathwaysmentioning
confidence: 62%
See 2 more Smart Citations
“…Based on findings in osteoblasts, it was proposed that P2X7 activation leads via PLD and PLA2 activation to LPA, and LPA, by activation of the LPA receptor (a GPCR), activates Rho (Panupinthu et al, 2007). Involvement of PLA2 activation in addition to an undefined Cl – channel in blebbing is supported by a recent study on macrophages (Janks et al, 2019).…”
Section: P2x7 Mediated Signaling Pathwaysmentioning
confidence: 62%
“…P2X7-mediated activation of cPLA2 and iPLA2 has been reported in immune and epithelial cells (Alzola et al, 1998; Chaib et al, 2000; Andrei et al, 2004; Kahlenberg and Dubyak, 2004; Garcia-Marcos et al, 2006b; Costa-Junior et al, 2011) and has been associated with various downstream effects such as PLD activation, kallikrein secretion, bioactive lipid generation, and pore formation as well as IL-1β processing, blebbing, and PS-flip (Garcia-Marcos et al, 2006b; Anrather et al, 2011; Costa-Junior et al, 2011; Norris et al, 2014; Wan et al, 2014; Alarcon-Vila et al, 2019; Janks et al, 2019). Janks et al (2019) recently reported an involvement of undefined chloride channels downstream of PLA2 in some of these processes. The mechanism of PLA2 activation by P2X7 remains unclear but was suggested to involve MAP kinases, P-I4 kinase/PIP2 (Garcia-Marcos et al, 2006b; Wan et al, 2014) and/or n-SMase activation in lipid rafts (Garcia-Marcos et al, 2006a).…”
Section: P2x7 Mediated Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In macrophages, P2X7Rs require anion channels to promote inflammation [ 50 ]. ATP is secreted by macrophages and microglia via volume-regulated anion channels (VRACs) [ 51 , 52 ], which may activate purinergic receptors.…”
Section: Resultsmentioning
confidence: 99%
“…However, this was later shown to be independent of the entry of cationic molecules via the receptor-channel and rather caused by a Ca 2+ /calmodulin-dependent current facilitation through some P2X7R orthologs (rat, but not human) (Roger et al, 2010) or the secondary activation of a chloride current e.g. in macrophages (Janks et al, 2019).…”
Section: P2x7 Receptormentioning
confidence: 99%